Rozwiązania instrumentalne controllingu w organizacjach dolnośląskich – wyniki badań - Zabłocka-Kluczka, Anna; Kral, Zygmunt; Bieńkowska, Agnieszka (Instrumental solutions of controlling in organizations of Low Silesia – results of research, 2008)
The results of research concerning the usage of controlling instruments in big organizations functioning on Low Silesia region were presented. Research referred to both organizations that impelmented controlling and do not have it yet. Results of reaserch related in particular to cost account, controlling profit and loss accounting, budgeting and software that can be used by controllers.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 446-462